The language of experience: a social analysis of the second new poetry - Koytak, Muhammet Elyesa. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
The Second New is the movement of innovation in the form of language in Turkish poetry in the second half of the 1950s. Acommon feature among the poets from different social backgrounds was their use of the technique of transforming of reality into an abstracted and obscure poetic diction. The Second New movement intersected with the social changes born of urbanization in the 1950s. However, the sociology in Turkey has not developed methodological tools ortheoretical frameworks which would allow objectifying the Second New phenomenon. This study makes a sociological contribution to that topic in the case of Cemal Süreya, a prominent poet of the movement. This study therefore focuses on the confrontation between the poet’s subjective dispositions and the objective conditions of the Turkish poetry field to explain the socio-genesis of the formal innovation in the poetic language. With this outlook, the inner development in Süreya’s poetry isanalyzed throughout his changing relationships with his external social world. The analysis showsthat the transformation of language as an innovation arose when the objective limits of the existing poetic capabilities of Turkish poetry did not allow Süreya to express his subjective dispositions, which are marked by harsh state policies and segregation from the established social order.It also showsthat the Second New is a response to the past, the reality and the context of which forced the poet to reinvent himself in the poetry within the major language.
Keywords: Turkish poetry -- 20th century -- History and criticism.